The Role of Queueing Discipline and Reneging in The Nigerian Banking Industry - Amaihian Augusta; Ogunnaike Olaleke; Mercy Ogbari; Olokundun Maxwell (Universitas Medan Area, 2022)
Queue discipline is a significant predictor of the effects of queuing efficiency on customer reneging in the queue system. The kind of queuing discipline adopted by a firm if not favourable to customers could discourage present customers from switching from one bank to the other where there will be less queues and better service delivery. This has been supported by Previous academic research observed that the kind of queue discipline adopted by a firm will greatly influence the waiting time for some set of customers. Also, find out that if a customer is aware that an organization employs the last in first out queue discipline most customers will refuse to arrive in a queue system early and this will in turn affect the behaviour of customers to the organization and also the outcome of the queue itself, as arriving customers are constantly receiving service correspondingly. It becomes important to ascertain in the Nigeria commercial bank environment the influence of’ queueing discipline on customers reneging in queuing system . This research adopted Quantitative approach for the survey in the study. The sampling techniques used for this study is simple random sampling techniques . A total of 400 copies of the questionnaire were distributed to the university students who are clients of the four (4) commercial banks, but only 384 (384) were returned and determined to be usable for the analysis. The following descriptive and inferential statistical techniques were used: The data received from the distributed questionnaire was analyzed using Multiple Regression. Based on these findings and gaps it was recommended that Bank management should adopt a kind of queueing discipline that is free and fair to all customers such as the first in first out queueing discipline. Banks should also be able to adopt the use of a computerized reservation system that will also handle problems resulting from customers overbooking their service and also find ways to encourage customers to visit their banking hall during off peak period.